An exploration of patients' perceptions and coping strategies for LBP. - Amanda Hall; Andrea Pike; Krystal Bursey; Sameh Mortazhejri; Andrea Patey; Jeremy Grimshaw; Holly Etchegary (PLoS ONE)
Background Evidence-based guidelines for managing LBP exist but their recommendations are often not used by health professionals in primary care. A key challenge to address this issue is understanding how people understand LBP, how they feel about it, and cope with it - particularly with regard to why they visit their doctors and their treatment expectations. This is important to understand, particularly since physician barriers to following LBP treatment guidelines have centered on patient issues (such as patient demand for imaging). Methods This was a qualitative, exploratory study using semi-structured interviews to explore patient perceptions of LBP and their coping strategies, paying particular attention to why patients with LBP in Newfoundland and Labrador (NL) seek care from family physicians and their treatment expectations, especially with regard to imaging. Eligible patients included adults aged 18 + years or older, living in both rural and urban settings in NL, Canada, who had visited their family physician about low back pain within the year prior to the interview. Researchers experienced in applying the Common-sense Model of Self-regulation (CSM), used the model to inform the development of our question guide and as a framework for the data analysis. Principal findings We found that new onset, severity, or persistent pain prompted patients to visit their family doctor, primarily to seek advice and/or a diagnosis, or for a referral to imaging or other providers. While patients believed that imaging was essential to understanding the underlying cause of their symptoms or informing their treatment, they were divided about its effectiveness - some felt it was beneficial to their treatment while others reported that it had no effect. We found that patients were unified in their largely negative views regarding prognosis and all experienced a range of negative emotions surrounding their LBP such as fear, stress, frustration, and guilt. We also found wide variation in understanding of cause and use of coping strategies. Patients posited several causes for the pain including injury, overexertion, comorbid conditions, and issues related to posture and sitting, and were split on their thoughts regarding prevention - about half thought it could be prevented, half did not. We found that patients coped with their LBP using a variety of strategies but were often disappointed in the results. Most reported no benefit to visiting their family doctors for their LBP. Some were pleased with their experiences with allied HCPs, noting small, but steady, improvements using recommended exercises but others were generally dissatisfied. Conclusion Our exploration of patient views and expectations for low back pain care indicates a mismatch between the care they are looking for and the care they receive. It also suggested a general lack of knowledge about the cause of LBP, the value and usefulness of imaging for its diagnosis and treatment, and poor physician-patient communication.